Inhibitory Effect of Bovine Adipose-Derived Mesenchymal Stem Cells on Lipopolysaccharide Induced Inflammation of Endometrial Epithelial Cells in Dairy Cows - Lu, Wengeng; Xu, Zheng-Mei; Liu, Qing; Yu, Nan-Nan; Yu, Jia-Bin; Li, Wei-Long; Mao, Ying-Ying; Du, Zhenzhen; Si, Linqing; Yuan, Siqi; Jin, Jidong; Fu, Shixin; et al. (Frontiers in Veterinary Science, 2021)
Endometritis is a disease that affects reproductive health in dairy cows and causes serious economic damage to the dairy industry world-wide. Although in recent years, the application of mesenchymal stem cell (MSC) therapy for the treatment of inflammatory diseases has attracted much attention, there are few reports of the use of MSCs in dairy cows. In the present study, our objective was to explore the inhibitory effects of bovine adipose-derived mesenchymal stem cells (bAD-MSCs) on lipopolysaccharide (LPS) induced inflammation in bovine endometrial epithelial cells (bEECs) along with the potential underlying molecular mechanisms. We characterized isolated bAD-MSCs using cell surface marker staining and adipogenic/osteogenic differentiation, and analyzed them using immunofluorescence, flow cytometry (surface marker staining), and adipogenic and osteogenic differentiation. Furthermore, to understand the anti-inflammatory effects of bAD-MSCs on LPS induced bEEC inflammation, we used a bAD-MSC/bEEC co-culture system. The results showed that bAD-MSC treatments could significantly decrease LPS induced bEEC apoptosis and pro-inflammatory cytokine expression levels, such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α). Furthermore, our results showed that bAD-MSC treatments could also significantly downregulate LPS induced p38, IkB-a, and JAK1 phosphorylation and Bax protein expression levels, which are closely related to inflammatory progress and cellular apoptosis in bEECs. Our findings demonstrate that bAD-MSCs play an inhibitory role in LPS induced bEEC inflammation and provide new insights for the clinical therapy of endometritis in dairy cows.